Stability Analysis of Marine Scaffold Under Coupled Environmental Loads - Pengkai Wang; Gang Yao; Yang Yang; Haiyang Qin (Journal of Marine Science and Engineering)
Structural instability in marine scaffold systems often causes serious economic losses and casualties. In this study, a multi-parameter coupled model was established based on the MIDAS GEN finite element analysis platform to investigate the influence mechanisms of key parameters on the overall stability of marine scaffold systems. To quantify the impact levels of the key parameters, a sensitivity analysis framework was established using an orthogonal experimental design approach and the corresponding compliance detection index and instability early-warning mechanisms were proposed. The results indicate that the overall stability of the scaffold system initially increases and then decreases with the rise in the adjustable base height. Variations in the cantilever length of the adjustable bracket within the range of 100–650 mm have no significant effect on the system’s overall stability. The absence of diagonal brace at the bottom, top, and facade ends significantly reduces structural stability. Increased vertical offset markedly degrades stability, whereas horizontal offset within ±5 mm has a negligible effect. The key parameters affecting the structural stability, ranked in descending order of significance, are as follows: absence of diagonal braces, verticality offset of the vertical bar, height of the adjustable base, horizontality offset of the horizontal bar, and cantilever length of the adjustable bracket. Finally, an early-warning assessment system for the scaffold structure was established. The research findings provide valuable guidance for optimizing marine scaffold design, enhancing construction safety, and formulating relevant standards and specifications.